(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Electrospun nanofibers is one of the new techniques that used recently in the treatment of skin wounds and diabetic foot ulcer, through the combination of biopolymer with synthetic polymer and formulated as nanofibers mat loaded antibacterial agent by using Electrospinning process, biopolymer and synthetic polymer such as Chitosan and PVA respectively. Loading of fusidic acid with various ratios of PVA/Chitosan to produce fusidic acid nanofibers that prepared in three dimensional structures to exert antibacterial activity against skin infections; the uniformity of drug/polymer ratio is important in production of nanofibers with acceptable diameter range. The characterization studies have been performed for morphology analysis, drug content, thermal analysis and in-vitro drug release profile from nanofibers to estimate the antibacterial activity of nanofibers on the wound site to assist in the skin healing process.